Impact of pelvic floor ultrasound in diagnosis of postpartum pelvic floor dysfunction: A protocol of systematic review - Wang, Fan-bo (Medicine (Baltimore), 2020)
BACKGROUND: This study will appraise the impact of pelvic floor ultrasound (PFU) in diagnosis of postpartum pelvic floor dysfunction (PPPFD). METHODS: Studies that report the impact of PFU in diagnosis of PPPFD will be examined in Cochrane Library, MEDLINE, EMBASE, PSYCINFO, Scopus, Web of Science, Allied and Complementary Medicine Database, CNKI, and WANGFANG up to June 1, 2020. Grey literature sources will also be searched. All potential case-controlled studies (CCSs) exploring the impact of PFU in diagnosis of PPPFD will be considered for inclusion in this study. Data will be extracted from eligible CCSs for data pooling and meta-analysis. Whenever necessary, we will also perform summary effect size, heterogeneity across studies, study quality assessment, and reporting bias. RESULTS: The present study will estimate pooled outcome effects regarding the impact of PFU in diagnosis of PPPFD. CONCLUSION: This study may provide robust evidence to judge the impact of PFU on PPPFD SYSTEMATIC REVIEW REGISTRATION: PROSPERO CRD42020187623.